The effect of population density on land use in the city of Shula D - A study in the geography of cities - (Journal of the College of Basic Education, 2023)
The concerned authorities in Iraq seek to develop the regions and develop them in line with the development of the world.There is no doubt that the development and revival of cities is part of this development. And you needIraqi cities need more studies and research to develop appropriate plans for the development of these cities.And standing on the problems and aspects of imbalances and since the city of the torch lacked moreStudies and research related to it, this research was an attempt to fill some gaps.The research presents the population density in the city of Al Shula and its impact on land use.And the services are intended to be abbreviated in accordance with the objectives of this study, and God is the conciliator.Research problem:The research problem can be formulated in the form of question (6), which is (what is the effect of population density onResidential and commercial land uses and service uses for transportation and education serviceshealth and others.